LEFT MOVEMENT IN YOGYAKARTA IN 1950-1965 - Wicaksono, Galih Agung (Walasuji : Jurnal Sejarah dan Budaya, 2020)
The national tragedy in 1965 claimed many victims, either parties related to the Movement of September 30th or their families. Yogyakarta is one of slaughtering acts of "left people" from other triangle areas, Bantul and Gunung Kidul. This study aims to reveal the local events -the Movement of September 30th 1965 in Yogyakarta- by emphasizing oral history so that the substance of history writing at the local level becomes more significant. This study uses qualitative analysis techniques and field research supported by interviews. The result of this study indicates that the destruction of the Movement of 30 September 1965 in Yogyakarta had begun since its inception, but it was still in the form of determination and enthusiasm, not in the form of physical action. However, after ABRI which led by Mayjen Soeharto, succeeded in freeing RRI, the destruction and pursuit of figures, actors, supporters and sympathizers of the Movement of 30th September 1965 was began.